Life and Works of Dr. Muhammad Hamidullah: An Overview - Samee-Ullah Bhat (P3M STAIN Kudus, 2018)
Dr. Muhammad Hamidullah was a prolific author whose imposing life in the field of writing was characteristically distinguished from other personalities and who devoted his life to religious and academic works and inspired many scholars for serving the cause of Islam. In modern times, it is also surprising enough for every scholar who observes the circumstances in which Dr. Hamidullah lived on one hand and the large number of valuable works produced by him about different subjects on the other hand with high academic standards. He has almost covered the whole range of Islamic studies in his writings and tried to explore true picture of Islam and its fundamental sciences. Although the dimensions of his works spread over all these spheres- theology, the holy Qur'an, Hadith, Fiqh, Islamic History and culture, ethics, politics, economics but hadith, Fiqh, Sirah and Islamic History were his favorite subjects. His contributions to these subjects were universally recognized in academic circles from the point of richness of material and high standard of research. In this research paper, an attempt is made to illustrate the life of Dr. Muhammad Hamidullah in a brief manner on one hand and an analysis of his major works on Sirah has been discussed on the other hand.